Trade liberalization, financial development, and economic growth: A panel data analysis on Turkey and the Turkic Republics - Mustafa Batuhan Tufaner (Universitas Islam Indonesia, 2022)
Purpose ― In this study, 5 Turkic Republics (Azerbaijan, Kazakhstan, Kyrgyzstan, Uzbekistan and Turkmenistan) and Turkey are analysed to investigate the impact of trade liberalisation and financial development on economic growth. Methods ― In this study, long-term relationships among trade liberalisation, financial development, and economic growth are analysed by applying unit root, cointegration and causality tests for panel data analysis study for the period 1998 to 2017. Findings ― The findings reveal a strong cointegration relationship between trade liberalization, financial development, and economic growth. It was understood that trade liberalisation positively affected economic growth, and financial development negatively affected economic growth in the long term for the whole panel. However, when the variables are analysed for each country in the panel, it is seen that the sign and severity of the coefficients change. Also, according to panel causality test results, it was understood that there was no causal relationship between variables. Implication ― This paper supports the notion that the direction of the relationship among trade liberalisation, financial development, and economic growth change according to countries in Turkey and the Turkic Republics. Originality ― This paper contributes to the literature by the general view that trade liberalisation and financial development are the driving force of economic growth; these relations may vary according to the country group examined in the studies, the period handled, and the econometric method applied.